Explaining the doubling of N2O emissions under elevated CO2 in the Giessen FACE via in‐field 15N tracing. (16th April 2018) - Moser, Gerald; Gorenflo, André; Brenzinger, Kristof; Keidel, Lisa; Braker, Gesche; Marhan, Sven; Clough, Tim J.; Müller, Christoph
Abstract: Rising atmospheric CO2 concentrations are expected to increase nitrous oxide (N2 O) emissions from soils via changes in microbial nitrogen (N) transformations. Several studies have shown that N2 O emission increases under elevated atmospheric CO2 (eCO2 ), but the underlying processes are not yet fully understood. Here, we present results showing changes in soil N transformation dynamics from the Giessen Free Air CO2 Enrichment (GiFACE): a permanent grassland that has been exposed to eCO2, +20% relative to ambient concentrations (aCO2 ), for 15 years. We applied in the field an ammonium‐nitrate fertilizer solution, in which either ammonium ( NH 4 + ) or nitrate ( NO 3 − ) was labelled with 15 N. The simultaneous gross N transformation rates were analysed with a 15 N tracing model and a solver method. The results confirmed that after 15 years of eCO2 the N2 O emissions under eCO2 were still more than twofold higher than under aCO2 . The tracing model results indicated that plant uptake of NH 4 + did not differ between treatments, but uptake of NO 3 − was significantly reduced under eCO2 . However, the NH 4 + and NO 3 − availability increased slightly under eCO2 . The N2 O isotopic signature indicated that under eCO2 the sources of the additional emissions, 8, 407 μg N2 O–N/m 2 during the first 58 days after labelling, were associated with NO 3 − reduction (+2.0%), NH 4 + oxidation (+11.1%) and organic N oxidation (+86.9%). We presume that increased plant growth and root exudation under eCO2 provided an additional source of bioavailable supply of energy that triggered as a priming effect the stimulation of microbial soil organic matter (SOM) mineralization and fostered the activity of the bacterial nitrite reductase. The resulting increase in incomplete denitrification and therefore an increased N2 O:N2 emission ratio, explains the doubling of N2 O emissions. If this occurs over a wide area of grasslands in the future, this positive feedback reaction may significantly accelerate climate change. Abstract : Scheme of changed C and N transformations (marked in red) in the GiFACE grassland after 15 years of elevated CO2 explaining the observed doubling of N2 O emissions. We presume that increased plant growth and root exudation under eCO2 provided an additional source of bioavailable supply of energy that triggered as a priming effect the stimulation of microbial soil organic matter (SOM) mineralization and fostered the activity of the bacterial nitrite reductase. The resulting increase in incomplete denitrification and therefore an increased N2 O:N2 emission ratio, explains the doubling of N2 O emissions in the GiFACE.